Analgesic efficacy and safety of ketamine after total knee or hip arthroplasty: a meta-analysis of randomised placebo-controlled studies. Issue 9 (13th September 2019) - Xu, Bei; Wang, Yilun; Zeng, Chao; Wei, Jie; Li, Jiatian; Wu, Ziying; He, Hongyi; Lei, Guanghua; Xie, Dongxing; Ding, Xiang
Abstract : Objective: To examine the analgesic efficacy and safety of ketamine after total knee or hip arthroplasty. Design: Systematic review and meta-analysis. Data sources: PubMed, EMBASE and Cochrane Library from inception to 22 May 2019. Eligibility criteria for selecting studies: Randomised controlled trials comparing the efficacy and safety of ketamine with placebo for postoperative pain relief in patients undergoing total knee or hip arthroplasty. Data extraction and synthesis: Data (ie, pain intensity, morphine consumption, gastrointestinal and psychotic adverse effects) were extracted by two reviewers independently. The Cochrane Collaboration's recommended tool was used to determine the methodological quality of included studies. Results: A total of 10 studies were included. One of them was rated as low quality. Compared with placebo, intravenous ketamine was effective for pain relief during 0–8-hour (weighted mean difference (WMD) −1.21, 95% CI −1.45 to −0.98, p<0.001; three studies, 149 participants) but not during 8–24-hour postoperative periods, and effective for reduction of cumulative morphine consumption during both 0–24-hour (WMD −17.76, 95% CI −31.25 to −4.27, p=0.01; five studies, 366 participants) and 0–48-hour (WMD −21.79, 95% CI −25.46 to −18.11, p<0.001; four studies, 252 participants) postoperative periods, without increasing risks of gastrointestinal or psychotic adverse effects. The limited data available for intra-articular (WMD −0.49, 95% CI −0.70 to −0.29, p<0.001; two studies, 83 participants) and epidural (WMD −2.10, 95% CI −3.30 to −0.90, p<0.001; one study, 20 participants) ketamine pointed to a significant reduction in pain intensity during 8–24-hour postoperative period. Conclusions: Intravenous administration of ketamine is effective and safe for postoperative pain relief in patients undergoing total knee or hip arthroplasty. Nevertheless, the analgesic efficacy and safety of ketamine in such patients seem to vary by different administration routes and still warrant further studies to explore.